Identification of the novel HLA‐C*07:315 allele. Issue 5 (24th September 2013) - Goldmann, K.; Lauer, B.; Spriewald, B. M.
<x xml:space="preserve">Abstract</x> The HLA‐C*07:315 allele is mostly identical to HLA‐C*07:09 but has a non‐synonymous substitution of C to G in exon 2.